Study of residual stress and microstructure evolution in magnesium alloy (WE43) due to deformation process via (PTCAP) / Mahmoud Sarhan Saddam Own - Mahmoud Sarhan, Saddam Own (2018)
In advanced industries, the demand of light and efficient parts in terms of structural integrity under particular mechanical purpose and aggressive environmental conditions has increased. Thus, requirement for a creative process that is aimed to upgrade metal material properties without adding additional weight or additives to the metal was a must. Several processes are categorized under the Severe Plastic Deformation (SPD) such as equal channel angular extrusion (ECAE), another method called equal channel angular pressing (ECAP), as well as high pressure torsion (HPT), and Parallel Tubular channel angular pressing (PTCAP). PTCAP is a recently developed and powerful plastic deformation method that is used to enhance the mechanical properties of the processed tubes. Residual stresses are generated inside the processed tubes during the deformation processes and could significantly influence or affect the mechanical performance of the final part. Thus, the effects of deformation process on residual stress, strain and to the crystallite size of Magnesium Alloy tubes was examined by means of X-Ray Diffraction (XRD). The results have shown that: residual stress was clearly changed from tensile stress before the deformation to compressive stress after the deformation process which means more crack resistance and better performance; the crystallite size shows reduction from 20.39